Retail Revolution - Bhatnagar, Gitanjali (Indian Journal of Marketing, 2004)
The country has witnessed a retail revolution in recent years. Significant development has taken place in urban areas in the form of organized retailing- mega stores or malls. Talk of any metro or a mini metro all of them now, have simply superb shopping malls to rule the shopper's heart. For example, in recent years Gurgaon near Delhi, has seen the mushrooming of so many swanky stores that a shoppers dream has come true. The city is all set to become the retail capital of the country. Actually, the corporate sector and the government, both have shown keen interest in the retail sector. This business suddenly seems promising to every one. In 2003 alone, a breathtaking 10 million sq.ft. of commercial space was picked up by the retail industry. McKinsey expects the organized sector to be around $18 billion by 2010.